Chinese consumers' understanding and use of a food nutrition label and their determinants. (April 2015) - Liu, Rongduo; Hoefkens, Christine; Verbeke, Wim
Highlights: Nutrition labels became mandatory instead of voluntary in China as of January 2013. Chinese consumers' understanding and use of food nutrition labels are analyzed. Familiarity with food nutrition labels associates with label understanding and use. Food nutrition label use decreases with increasing BMI. Subjective rather than objective understanding associates with label use. Abstract: This paper investigated Chinese consumers' understanding and use of the Chinese food nutrition label and their determinants. Quantitative data were collected during March 2012 through a self-administrated structured questionnaire conducted in Beijing ( n = 213) and Baoding city ( n = 447). Questions assessed Chinese consumers' use and understanding (objective and subjective) of food nutrition labels, nutrition knowledge (objective and subjective), socio-demographic characteristics, diet status, diet-health awareness, body mass index (BMI) and familiarity with food nutrition labels. A moderate degree of subjective understanding and a low degree of objective understanding of food nutrition labels were found among the participants, and 70% of the participants claimed to rarely or never use nutrition labels when shopping for food. Nutrition knowledge (objective and subjective) positively affected participants' understanding (objective and subjective) of food nutrition labels. Familiarity with food nutrition labels had a strong positive effect on understanding of and use of food nutrition labels. Subjective nutrition knowledge and subjective understanding also played a significant and positive role in Chinese consumers' label use. Age yielded a negative effect on both subjective and objective understanding, while education only affected participants' objective understanding. None of the socio-demographic characteristics associated with self-reported use. Implications for future policies to improve Chinese consumers' understanding and promote their use of food nutrition labels are discussed.